Ancestral Hybridization Yields Evolutionary Distinct Hybrids Lineages and Species Boundaries in Crocodiles, Posing Unique Conservation Conundrums - Pacheco-Sierra, Gualberto; Vázquez-Domínguez, Ella; Pérez-Alquicira, Jessica; Suárez-Atilano, Marco; Domínguez-Laso, Jerónimo (Frontiers in Ecology and Evolution, 2018)
Interspecific hybridization can lead to adaptation and speciation, especially in the context of recent radiations. The emblematic Crocodylus (true crocodiles) is the most broadly distributed, ecologically diverse, and species-rich crocodylian genus. Nonetheless, their within-species evolutionary processes are poorly resolved mainly due to their potential for hybridization. Notably, the evolutionary outcomes when hybridization is ancient and involves long-lived species, like crocodiles, remain largely unexplored. Here, we evaluate the genomic admixture between the American (Crocodylus acutus) and the Morelet’s (Crocodylus moreletii) species, and demonstrate that this hybridization system challenges the definition of species boundaries and poses a triple conservation conundrum: what has been recognized as C. acutus is actually two distinct species, therefore its taxonomic reassessment is needed; we identified two evolutionary distinct hybrids lineages, which are genetically discernible from the parental species; the remaining C. moreletii populations evidence its likely extinction as a species and/or evolution via hybridization. Hence, the crocodiles’ distinct species and hybrids lineages warrant recognition and need urgent conservation efforts.